Employments of the "standard pattern" in Yoruba music - King, Anthony (International Library of African Music, 1960)
The purpose of this article is to show some of the uses of the “Standard Pattern” in Yoruba traditional music. Among most African races this pattern is relegated to those instruments forming a rhythmic bond between the song (if any) and the drumming. Thus we usually find it performed on metal bells and gongs, rattles and allied instruments, or by handclapping. The Yoruba music in question, drawn from the Ekiti area, does not permit the mixing of any alien sounds with those of the drums, the only and obvious exception being the voices of the singers rendering the song. This means that gongs, bells, rattles and handclapping are never employed in any performance in which the drums are used.
Keywords: Yoruba (African people); Music; Drum; Dynamics; Drum music; Performance; Ethnomusicology; Musical instruments; Interpretation; Yoruba Art; Nigeria; African Music; Drum (Instrument)